Promoter specificity of the two transcriptional activation functions of the human oestrogen receptor in yeast - Daniel Metzger; Régine Losson; Jean‐Marc Bornert; Yves Lemoine; Pierre Chambon (1992)
We have previously demonstrated that the human oestrogen receptor (hER) contains two transcriptional activation functions located in the N-terminal region (TAF-1) and in the hormone binding domain (TAF-2), which can act both independently and synergistically in a promoter-and cell-specific manner in animal cells. We have also demonstrated that hER can activate transcription from chimaeric oestrogen-responsive GAL1 promoters in yeast, and shown that transcriptional activation was due to TAF-1, whereas TAF-2 showed little, if any, transcriptional activity on these promoters. By using a more complex promoter derived from the URA3 gene, we now show that TAF-2 is also active in yeast, and that the activities of TAF-1 and TAF-2 are promoter-context-specific in yeast. We also confirm that the agonistic activity of 4-hydroxytamoxifen (OHT) can be ascribed to the activity of TAF-1.